2000
DOI: 10.1007/bf02720082
|View full text |Cite
|
Sign up to set email alerts
|

Conductivity, dielectric behaviour and magnetoelectric effect in copper ferrite-barium titanate composites

Abstract: Composites of CuFe 2 O 4 and BaTiO 3 were prepared using a conventional ceramic double sintering process. The presence of both phases was confirmed by X-ray diffraction. The variations of resistivity and thermo emf with temperature in these samples were studied. All the composites showed n-type behaviour. The variation of dielectric constant (ε′) in the frequency range 100 Hz to 1 MHz and with temperature at constant frequency were studied. The conduction phenomenon was explained on the basis of a small polaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(49 citation statements)
references
References 13 publications
4
45
0
Order By: Relevance
“…In the past two decades, various particulate composites consisting of piezoelectric and magnetostrictive materials with different connectivity schemes including "3-0" and "2-0" have been reported: such as CoFe 2 [26][27][28][29][30][31][32]. Table 2 provides a brief list of results obtained on these composite materials.…”
Section: Sinteringmentioning
confidence: 96%
See 1 more Smart Citation
“…In the past two decades, various particulate composites consisting of piezoelectric and magnetostrictive materials with different connectivity schemes including "3-0" and "2-0" have been reported: such as CoFe 2 [26][27][28][29][30][31][32]. Table 2 provides a brief list of results obtained on these composite materials.…”
Section: Sinteringmentioning
confidence: 96%
“…Table 2 lists some of the composite materials reported in literature, their magnitude and experimental conditions. [14,[24][25][26][27][28][29][30][31][32][33][34] It can be seen from this table that at low frequencies the magnitude of the ME effect can be as large as 115 mV/ cm·Oe: which is ∼300 times higher than that of Cr 2 O 3 . Tables 3, 4 and 5 provide a list of magnetostrictive and piezoelectric materials of interest.…”
Section: Introductionmentioning
confidence: 94%
“…Since most of researches on ferrites highlight on the development of advanced ferrite materials which satisfy specific requirements in different industrial applications, many attempts have been done to synthesize and investigate pure and substituted copper ferrite [1][2][3][4][5][6][7]. It was found that such kinds of ferrites are characterized by a spinel structure with high thermodynamic stability, electrical conductivity and high catalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Though some materials with coupling between electrical and magnetic ordering (i.e., a change in an external electric field induces magnetic properties, or vice versa) are rare, they are very promising from points of view of their science and technological applications [3][4][5][6][7]. Lead iron niobate Pb(Fe 1/2 Nb 1/2 )O 3 (PFN) is one of these materials whose high dielectric constant, ferroelectric and antiferromagnetic properties have been reported long ago [8,9].…”
mentioning
confidence: 99%